Hubungan Kemampuan Literasi Numerasi dengan Hasil Belajar Matematika Siswa Kelas V SD Gugus II - Fadly Afandi; Muh Idris Jafar; Adnan K (Universitas Negeri Makassar, 2021)
The purpose of this study was to determine whether or not there was a significant positive relationship between numeracy literacy skills and mathematics learning outcomes for fifth grade elementary school students. The method used is quantitative research with a correlational model. The research data were obtained by distributing numeracy literacy test questions to students. Based on the t-test, the results of tcount = 12, 36448 are greater than ttable = 1.66462 with a significance level of 5%. The conclusion of this study is that there is a significant positive relationship between numeracy literacy skills and mathematics learning outcomes for fifth grade elementary school students in cluster II. Based on these conclusions, the impact obtained in this study is to determine the level of a significant relationship between literacy ability and mathematics learning outcomes for fifth grade students so that this will have an impact that at the school the teacher knows that it turns out that good numeracy literacy skills will produce good learning outcomes. also for students.